A NEW SAUROPTERYGIAN REPTILE WITH PLESIOSAURIAN AFFINITY FROM THE LATE TRIASSIC OF ITALY (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2006)
Bobosaurus forojuliensis, gen. et sp. nov., is a large sauropterygian from the Alpine Late Triassic (Early Carnian, northeastern Italy). The holotype is a moderately disarticulated skeleton consisting of the tip of the rostrum, part of the neck (including the atlas-axis complex), the trunk, most of the tail, parts of the limbs, and the pelvic girdle. The new taxon is characterized by a mosaic of "nothosaurian" and "plesiosaurian" features. It exhibits characters that were previously considered autapomorphies of different sauropterygian taxa. Dorsal neural spines are very high as in Nothosaurus mirabilis, and each dorsal rib has a distinct uncinate process, a diagnostic feature of the placodont Paraplacodus. The atlas-axis complex has the plesiosaurian pattern but is peculiar in several details. The neural spines of the anterior cervicals have an arched anterior margin. The spade-shaped pubis lacks an obturator foramen and an articulation with the ilium, and is associated with a stout, "hourglass-shaped" ilium that has a twisted shaft. Apomorphic characters include: cervical centra higher than wide and "pear-shaped" in anteroposterior view, a peculiar zygapophyseal articulation of pectoral to "caudal" vertebrae like that found in the dorsal vertebrae of Simosaurus, but with a reversed anteroposterior polarity, high neural spines on all vertebrae, neural spine of "sacral" to mid-caudal vertebrae with a bottle-shaped profile in lateral view, peculiar mid-posterior cervical ribs, lightened skeleton, and a comparatively large humerus. The new taxon was a specialized surface swimmer with a stiffened trunk and large forelimbs. It represents one of very few Late Triassic eusauropterygian taxa. It is probably a pistosaurid or, alternatively, could represent a different clade closer to Plesiosauria, occurring in the gap between the late Anisian pistosaurids and the earliest Rhaetian plesiosaurs.